Implementation of lung cancer screening: promises and hurdles - Prosch, Helmut (Translational Lung Cancer Research; Vol 3, No 5 (October 21, 2014): Translational Lung Cancer Research [The 14th Central European Lung Cancer Congress (CELCC)], 2014)
Lung cancer screening is a subject of considerable interest in the medical community and the general population. Since the publication of the data from the national lung screening trial (NLST) in 2011, the interest in lung cancer screening has increased even more. Data from many sources provide evidence that low-dose computed tomography (LD-CT) lung cancer screening can be performed with even greater efficacy if inclusion criteria as well as nodule management are optimized. There are, however, also a number of potential hurdles for the implementation of lung cancer screening. Among these are, in particular, the high prevalence of screen-detected pulmonary nodules, the unknown extent of over-diagnosis, the potential harms of the cumulative radiation dose and the insufficient data on cost-efficiency of lung cancer screening. In this article, the most recent insights into some of the most imminent questions are reviewed to provide an understanding of the challenges we still face in lung cancer screening.